Towards healthy settings for people with intellectual disabilities. (26th June 2019) - Vlot-van Anrooij, Kristel; Naaldenberg, J; Hilgenkamp, T I M; Vaandrager, L; van der Velden, K; Leusink, G L
Abstract: People with intellectual disabilities (ID) depend on their environment for support to live healthily. The characteristics of healthy settings for people with ID are unknown. This study aims to conceptualize healthy settings for people with ID by conducting an international and multidisciplinary concept mapping study. As theoretical framework the settings approach, an ecological model with a whole system focus toward health promotion, was used. The integrative mixed-methods approach of this study involved concept mapping with researchers specialized in healthcare for people with ID and researchers specialized in healthy settings. The 41 participants generated statements that were later sorted and rated. Findings encompass 13 clusters relating to the social environment, the physical environment and societal preconditions. Specific factors of healthy settings for people with ID include: (i) universal design of the physical environment, (ii) the role of care professionals in the social environment to empower people with ID, (iii) possibilities for care providers to contribute to a health-promoting setting and (iv) preconditions that allow people to engage in society. These factors can be used in strategies to apply the approach in practice and give directions to put in place policies on developing enabling environments and decreasing health inequities.